The Turn – Integration of Information Seeking and Retrieval in Context - Frøkjær, Erik (Dansk Biblioteksforskning, 2005)
ANMELDELSE: Ingwersen, P & Järvelin, K (2005). The Turn - Integration of Information Seeking and Retrieval in Context, The Kluwer International Series on Information Retrieval, Springer